ТАЛАБАЛАРДЫҢ КӘСИПЛИК СЫПАТЛАРЫН ҚӘЛИПЛЕСТИРИЎДЕ МИЛЛИЙ ҚӘДРИЯТЛАРЫҢ ТУТҚАН ОРНЫ - Кутлымурадов, К.А. (SCIENCE and SOCIETY, 2019)
The article outlines the issues of students’ education, the principles of constructing the concept of values in the process of teaching students and the formation of their professional qualities.
Keywords: world community; qualified personnel; human qualities; universal values; kinship; life experience; parental advice; disabled child; historical traditions